Analysis of Spread Moored FPSO-Tanker Side-by-Side System with Offloading Operability - Irawan, R. (Springer Science and Business Media Deutschland GmbH, 2021)
Dynamic load acting on the side-by-side mooring system is one of the important factors to estimate the offloading operability of the FPSO. In this paper, a numerical mooring analysis for the side-by-side moored FPSO-tanker system is investigated. Floating Structure analysis is divided into two parts. The first is to calculate the hydrodynamic coefficient, and the second part is calculating the system responses in the time-domain analysis. The prediction of FPSO-Tanker responses is necessary during offloading. This research presents the possibility of the use of Artificial Neural Networks model for the prediction of the responses of FPSO-Tanker system with spread-mooring configuration. The ANN model considering various metocean data such as azimuth angles, significant wave height, wind load, swell, hawser and the mooring configurations. The results of this study indicated that the ANN model shows an accurate prediction of the FPSO-tanker response that are required for the design of side-by-side vessels during offloading. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.